GURU GARDA DEPAN PENDIDIKAN ANTI KORUPSI - Baroroh, Charunie (PKn Progresif, 2008)
The value of anti-corruption educational values such as discipline, responsibility, honesty, fairness is self competence must exist and be developed by all teachers, in addition to professional competence should be done with hard work, discipline, daring, simple and independent. Naturally, the value is inherent in the nature of teachers who have the task of instilling noble values in students in the teaching task. Teachers as changing agents, as the main door to success should have a strong conviction to realize success in forming the character of generations of anti-corruption, they are in the vanguard of anti-corruption education.